Optimization Problem on Permutations with Linear-Fractional Objective Function: Properties of the Set of Admissible Solutions - Emets, O. A.; Kolechkina, L. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider an optimization problem on permutations with a linear-fractional objective function. We investigate the properties of the domain of admissible solutions of the problem.